Sensorless position control of induction machines using high frequency signal injection - Teske, Nikolas (2001)
The aim of this research project was to develop a position controlled induction machine vector drive operating without a speed or position sensor but having a dynamic performance comparable to that of a sensored position vector drive. The methodology relies on the detection of a rotor saliency in the machine by persistent high-frequency voltage injection. The rotor position is then estimated from the resulting stator current harmonics that are modulated by the spatial rotor saliency. This can be a built-in rotor saliency (a designed asymmetry) or the natural saliency due to rotor slotting. This project investigates the demodulation of the extracted high-frequency current spectrum and different topologies for the estimation of rotor position.